Camarillo State Hospital Members of the Board Luncheon
This document is an invitation to all Camarillo State Hospital Members of the Board to lunch. The event will take place in the Bank of California (National Association) located in 550 South Flower Street at Sixth. The hosts are: Mr. Peter Ulrich (Senior Vice President The Bank of California); Louis A. Baptista (Member of the Board). List of guests: Alfreda Teague; Francis W. Hertel; John S. Broome; Lewis R. Nash; John Sheel; Jack W. Thompson; Ken Mills; Baxter Ward.